2017
DOI: 10.4103/0366-6999.206349
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Analysis of 102 Patients with Synchronous Colorectal Cancer and Liver Metastases Treated with Simultaneous Resection

Abstract: Background:The liver is the most common site for colorectal cancer (CRC) metastases. Their removal is a critical and challenging aspect of CRC treatment. We investigated the prognosis and risk factors of patients with CRC and liver metastases (CRCLM) who underwent simultaneous resections for both lesions.Methods:From January 2009 to August 2016, 102 patients with CRCLM received simultaneous resections of CRCLM at our hospital. We retrospectively analyzed their clinical data and analyzed their outcomes. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The prognosis of patients with CRLM with simultaneous resection of CRC and liver metastases is still not satisfactory. Overall, 75% (7) of patients still experience recurrence after surgery; the 5-year progression-free survival (PFS) and OS rates are only 21.2% and 46.4%, respectively (8). The incidence rates of postoperative complications and major complications are approximately 47% and 12% (9).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with CRLM with simultaneous resection of CRC and liver metastases is still not satisfactory. Overall, 75% (7) of patients still experience recurrence after surgery; the 5-year progression-free survival (PFS) and OS rates are only 21.2% and 46.4%, respectively (8). The incidence rates of postoperative complications and major complications are approximately 47% and 12% (9).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is no significant difference between the two surgical strategies regarding short-term and long-term outcomes (10,11,20,21). Our experiences from the clinical practice at our center attest to safety and efficacy of treating CRLM patients using simultaneous surgical resection (13,14). Moreover, the ideal surgical procedure and incision approach for the simultaneous resection of CRLM, in which various types of incisions have been applied, is still controversial.…”
Section: Discussionmentioning
confidence: 86%
“…Currently, surgical resection remains the best treatment option for colorectal liver metastases (CRLM) (4), with markedly improved overall survival and long-term outcomes (5)(6)(7). Although the vast majority of patients with colorectal cancer and liver metastases have unresectable disease (8,9), with the development of surgical techniques and the use of laparoscopy, there is an increasing number of studies supporting the simultaneous resection of colorectal cancer and liver metastasis as feasible and safe (10)(11)(12)(13)(14)(15). Nevertheless, the surgical procedure of a simultaneous resection could still be improved, for example, the incision type.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed resection often compromises overall survival (27). Moreover, Zhang et al (28) and Silberhumer et al ( 29) also concluded that simultaneous surgical resection is a safe and effective treatment option for patients with CRC LM. Compared with staged surgery, there was no significant difference in the longterm prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%